2014
DOI: 10.4238/2014.july.4.17
|View full text |Cite
|
Sign up to set email alerts
|

MDR1 C3435T polymorphism in Mexican patients with breast cancer

Abstract: ABSTRACT. We investigated whether the MDR1 C3435T polymorphism is associated with fibrocystic changes (FCC), infiltrating ductal breast cancer (IDBC), and/or clinical-pathological features of IDBC in Mexican patients. Samples from women who received surgical treatment in 2007 at the Centro Médico de Occidente (México) were included in the analysis. Genotyping was performed by polymerase chain reaction-restricted fragment length polymorphisms in 64 paraffin-embedded breast samples with IDBC, 64 samples with FCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
(28 reference statements)
1
5
0
2
Order By: Relevance
“…In agreement with a number of previous reports [16, 18, 21, 23, 24], our findings revealed no significant association between this polymorphism and breast cancer development. Otherwise, Gutierrez-Rubio et al [24] did not find differences in the distribution of C3435T polymorphism between breast cancer patients and controls.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with a number of previous reports [16, 18, 21, 23, 24], our findings revealed no significant association between this polymorphism and breast cancer development. Otherwise, Gutierrez-Rubio et al [24] did not find differences in the distribution of C3435T polymorphism between breast cancer patients and controls.…”
Section: Discussionsupporting
confidence: 93%
“…In this line, Turgut et al [13], Wu et al [20] and Macías-Gómezdid et al [23] have reported similar results. However, Ghafouri et al have found a significant correlation between ABCB1 C3435T polymorphism and clinical grades of breast cancer with higher grade in CC carriers ( P  = 0.027) [25].…”
Section: Discussionmentioning
confidence: 57%
“…Zubor et al (2007), reported that, among patients in Slovak Republic, those carrying CC genotype of C3435T had increased risk of breast cancer. In a study by Macias-Gomez et al (2014) conducted among Mexicans the prevalence of the TT genotype was 8% for patients with fibrocystic changes (FCC), 13% for infiltrating ductal breast cancer (IDBC) and 24% for control samples.…”
Section: Discussionmentioning
confidence: 99%
“…Other clinicopathological features in this study were not significantly related to ABCB 1 C3435T polymorphisms. Turgut et al [ 36 ], Wu et al [ 9 ] and Macías-Gómezdid et al [ 37 ] reported similar results. The correlation between the clinicopathological features of breast carcinoma in our study, according to ABCG 2 C421A polymorphism revealed no significant association at this level.…”
Section: Discussionmentioning
confidence: 61%